(untitled) (Annals of Medical Research, 2023)
Aim: In children, a broad range of paroxysmal events, including syncope and arrhythmias, may mimic true epileptic seizures. When a definitive diagnosis could not be established, long-term video electroencephalogram monitoring (LTVEM) should be taken into consideration. Furthermore, epilepsy patients have a higher rate of cardiac comorbidities. The purpose of this study is to evaluate the rationale and results of the pediatric cardiology consultations in patients admitted to the LTVEM unit. Materials and Methods: We retrospectively analyzed the files of children who were admitted to LTVEM unit and consulted with the pediatric cardiology department between January 2006 and May 2014. The patients who had both echocardiography and 24-hour ambulatory electrocardiogram monitoring were included. Results: Among 70 children, 74.3% (n: 52) were classified as having epilepsy, 21.4%. (n: 15) with nonepileptic events, and 4.3% (n: 3) could not be classified. In epilepsy group, 21 children (40.4%) were consulted with pediatric cardiology due to rhythm disturbances detected during LTVEM, the remaining consultations (59.6%) were due to history of known cardiac diagnosis (arrhythmias n: 2, structural/congenital heart disease n: 5), tuberosclerosis (n: 6), drop attacks (n: 5), murmur (n: 5), and other reasons. The cardiac evaluation revealed previously undetected arrhythmia (n:3) and mitral valve prolapse (n:1) in four patients with epilepsy. In addition to the pre-existing long QT syndrome, one child experienced his typical attack, subsequently he was diagnosed as epilepsy. The remaining group consisted of 18 children, with syncope being the most common diagnosis for consultation (n: 10, 55.5%). Conclusion: Our study revealed that a subgroup of children with epilepsy had cardiovascular comorbidities. Additionally, epilepsy was confirmed in some patients who already had cardiac problems. Pediatricians should be aware of potential mimickers of epilepsy and note that epilepsy and cardiac problems may also co-exist. Correct diagnosis and appropriate treatment are crucial in this patient group.